Nudge Theory Misuse and Greenwashing in H&M’s Garment Collecting Program for Circular Fashion - Feby Rachma Alfi Dhiandra; Andes Ismayana; Perdinan Perdinan (CV. Publikasi Indonesia, 2026)
This paper critically examines H&M's Garment Collecting Program as a behavioural intervention framed under circular fashion and sustainability. The study investigates whether the scheme functions as an ethical application of nudge theory or operates as a pseudo-nudge and behavioural prod that reinforces fast fashion consumption under a green narrative. Using a qualitative descriptive case study, the research draws on desk-based analysis of H&M's official communications, sustainability reports, voucher terms, and relevant academic and analytical sources. Qualitative content analysis is applied to assess four key dimensions of the program's design and communication: transparency of information, structure and strength of incentives, temporal conditions shaping decision-making, and the moral framing of participation. The findings show that the program relies predominantly on Type 1 nudges that trigger automatic responses through immediate discounts, limited transparency regarding post-collection material flows, and simplified claims of circular impact. This configuration facilitates moral licensing and generates psychic cost, enabling consumers to feel ethically compensated while remaining embedded in high-volume consumption patterns. When combined with strong purchase-oriented incentives and constrained resistibility, the intervention aligns more closely with pseudo-nudging and behavioural prodding, and supports a diagnosis of greenwashing by design. The paper argues that ethically robust nudging in circular fashion requires transparent intent, easily resistible choice architectures, proportionate incentives, and verifiable environmental outcomes, and offers principles for redesigning garment collection schemes accordingly.